Three-generation super no-scale models in heterotic superstrings - Ioannis Florakis; John Rizos; Konstantinos Violaris-Gountonis (Physics Letters B, 2022)
We derive the conditions for the one-loop contribution to the cosmological constant to be exponentially suppressed in a class of heterotic string compactifications with three generations of chiral matter, where supersymmetry is spontaneously broken à la Scherk-Schwarz. Using techniques of partial unfolding based on the Hecke congruence subgroup Γ0(2) of the modular group to extract the leading asymptotics, we show that the super no-scale condition nB=nF between the degeneracies of massless bosons nB and fermions nF in the full string spectrum is necessary but not sufficient, and needs to be supplemented by additional conditions which we identify. We use these results to construct three-generation Pati–Salam models with interesting phenomenological characteristics.